SUSTAINABILITAS KINERJA FINANSIAL: STUDI DALAM PERSPEKTIF KNOWLEDGE MANAGEMENT, TALENT DEVELOPMENT, DAN MODAL SOSIAL - Pujo Sugito; Kamaluddin Kamaluddin (University of Merdeka Malang, 2014)
The aim of this research was to explore the financial performance sustainability of small and medium industriesin perspective of knowledge management, talent development and social capital. The population in thisstudy was all small and medium industries in the district of Tulungagung, East Java. The number of sampleswas 100 respondents. The purposive random sampling technique was used to collect data. Furthermore, thedata was analyzed by descriptive and inferential technique analysis and Structural Equation Modeling (SEM).Factor analysis on SEM was used to confirm the most dominant variable in one group. Regression weight onconfirmatory SEM was used to examine how much the relationship between variables. The results of dataanalysis showed that the three research hypotheses that had been formulated statistically were accepted. Firstin detail, the better the knowledge management was, the better the financial performance sustainability (CR =2,896 and P = 0,001) was. Second, the better the talent development was, the better the financial performancesustainability of (CR = 2,734 and P = 0,003) was, and third, the higher the intensity of social capital was, thehigher the financial performance sustainability (CR = 2,221 and P = 0,020) was. It meant that all factors hadto be concerned to develop the small and medium industries.